(untitled) (International Journal of Engineering and Computer Science, 2014)
Cell Phone Based WSN of compressed micro- sensors for data acquirement supervise some surroundings distinctiveness, such as noise, trembling, temperature, and strain. These sensors are entrenched devices accomplished of data communication. In numerous of applications, sensor nodes are deployed over a geo-graphically large region. Due to their configuration, data of measured values must be transferred among stations through these sensor nodes. For this reason a successful, energy efficient routing protocol should be implemented to avoid data loss and additional challenges within limited energy levels. This paper presents a mobility based routing algorithm for wireless sensor networks, based on the selection of the scheme of dynamic nodes. The key objective is to boost the lifetime of a sensor network while not compromising data delivery. Significant tasks such as, scrutinize, supervise and determining of energy levels of nodes are handled by these independent mechanisms